Janeway's immunobiology - Murphy, Kenneth; Travers, Paul, 1956-; Walport, Mark; Janeway, Charles (New York : Garland Science, 2012)
This is a textbook that introduces the immune system in all its aspects to undergraduates, and also provides a treatment of the subject that is comprehensive enough to be useful to graduate students interested in research, and to medical students focused on clinical applications. The Eighth Edition has been thoroughly revised and updated.
Basic concepts in immunology -- Innate immunity: the first lines of defense -- The induced responses of innate immunity -- Antigen recognition by b-cell and t-cell receptors -- Antigen presentation to t-lymphocytes -- Signaling through immune-system receptors -- The development and survival of lymphocytes -- T cell-mediated immunity -- The humoral immune response -- Dynamics of adaptive immunity -- The mucosal immune system -- Failures of host defense mechanisms -- Allergy and allergic diseases -- Autoimmunity and transplantation -- Manipulation of the immune response.
Prev. ed. 2008.
Includes bibliographical references and index.
Keywords: Immunology; Immune System -- physiology; Immune System -- physiopathology; Immunity; Immunotherapy